Discovery of Novel UV-Filters with Favorable Safety Profiles in the 5-Arylideneimidazolidine-2,4-dione Derivatives Group - Popiół, Justyna; Gunia-Krzyżak, Agnieszka; Piska, Kamil; Żelaszczyk, Dorota; Koczurkiewicz, Paulina; Słoczyńska, Karolina; Wójcik-Pszczoła, Katarzyna; Krupa, Anna; Kryczyk-Poprawa, Agata; Żesławska, Ewa; Nitek, Wojciech; Żmudzki, Paweł; et al. (Molecules (Basel, Switzerland), 2019)
Effective protection from the harmful effects of UV radiation may be achieved by using sunscreens containing organic or inorganic UV filters. The number of currently available UV filters is limited and some of the allowed molecules possess limitations such as systemic absorption, endocrine disruption properties, contact and photocontact allergy induction, and low photostability. In the search for new organic UV filters we designed and synthesized a series consisting of 5-benzylidene and 5-(3-phenylprop-2-en-1-ylidene)imidazolidine-2,4-dione (hydantoin) derivatives. The photoprotective activity of the tested compounds was confirmed in methanol solutions and macrogol formulations. The most promising compounds possessed similar UV protection parameter values as selected commercially available UV filters. The compound diethyl 2,2′-((Z)-4-((E)-3-(4-methoxyphenyl)allylidene)-2,5-dioxoimidazolidine-1,3-diyl)diacetate (4g) was characterized as an especially efficient UVA photoprotective agent with a UVA PF of 6.83 ± 0.05 and favorable photostability. Diethyl 2,2′-((Z)-4-(4-methoxybenzylidene)-2,5-dioxo- imidazolidine-1,3-diyl)diacetate (3b) was the most promising UVB-filter, with a SPFin vitro of 3.07 ± 0.04 and very good solubility and photostability. The main photodegradation products were geometric isomers of the parent compounds. These compounds were also shown to be non-cytotoxic at concentrations up to 50 µM when tested on three types of human skin cells and possess no estrogenic activity, according to the results of a MCF-7 breast cancer model.